Differentielle Aspekte der Bewegungsorganisation im Volleyball - Heinen, T.; Velentzas, K. (Leipziger Sportwissenschaftliche Beiträge, 2005)
The purpose of this investigation is to address questions to differential aspects of the movement organization in volleyball. In this study the spiking movements of 17 female Volleyball players were analyzed cinematographically (3D) and examined with regard to their movement patterns. Additionally the structure of movement representations was analyzed in each individual case. Different movement strategies and distinctive features of the mental representations can be identified. Consequences of the results for the understanding of the spiking movement in volleyball will be discussed.